Javaserver Pages. - 2nd Edition - Bergsten, Hans (O'Reilly, 2011)
Since its inception in 1999, Enterprise Java has taken the Java programming community by storm--developers have realized its potential for building distributed applications. Today, JavaServer Pages (JSP) continues to harmonize how web designers and programmers create dynamic web sites. JSP builds on the popular Java servlet technology and makes it easier to develop dynamic web applications--even if you're not a hard-core programmer.